Upgrading Monitoring system of Higher Educational Quality in the Republic of Kazakhstan. - Eleusov, A. A; Alzhanova, N. Sh. (Journal of Economic Research & Business Administration, 2015)
Education nowadays requires new directions and new technologies. This issue can be dealt by upgrading education quality. Education quality of higher educational institutes in Kazakhstan needs profound examination and evaluation. In this article, we try to find ways to improve Kazakhstani education and upgrade educational system. Quality indexes of higher education are analyzed and a series of recommendations are presented. To be Exact, a basis for conducting accreditation activities for higher education quality is worked out. Meanwhile, a state function designed based on concrete elements aimed at improving education quality in higher educational institutes.